Leveraging AI for Enhanced Product Life Cycle Management (PLM) Transformation - Krishna Jayant Baride, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative potential of Artificial Intelligence (AI) and Generative AI in Product Lifecycle Management (PLM) transformation. It begins by examining the current challenges in PLM, including the difficulties in understanding existing processes, identifying inefficiencies, and preparing for future states. The article then delves into how AI technologies can address these challenges, offering solutions such as automated process learning, intelligent inefficiency detection, and assistance in creating standard operating procedures. The benefits of AI-enhanced PLM are discussed, highlighting improved efficiency, faster transformation processes, and enhanced product quality. The article also covers implementation strategies, emphasizing the importance of integrating AI tools into existing systems and addressing training and adoption challenges. A section on continuous improvement through AI showcases how these technologies enable real-time monitoring, bottleneck resolution, and iterative enhancements. Finally, the article looks towards the future, discussing emerging AI technologies in PLM, potential barriers to widespread adoption, and important ethical considerations. Throughout, the article underscores the significant impact AI can have on PLM processes, while also acknowledging the challenges that organizations must navigate to successfully leverage these technologies.
Keywords: AI-Enhanced PLM; Generative AI in Product Development; Continuous Improvement through AI; PLM Transformation Challenges; AI Implementation Strategies in PLM